Educational Communication Management of Civil Service Police Unit Members In The Community of Kerinci District - Maruli Hutagalung; A As’ad; Abd. Malik; S Sodiah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The Civil Service Police Unit carries out service duties as educators and caretakers for the community. Civil Service Police Unit has been seen as tough and rude up to now, but Kerinci Civil Service Police Unit members are tasked with prioritizing human values to make people trust and obey government regulations. This discuss members' communication strategies in educating public, using a descriptive qualitative approach and case study research on the Civil Service Police Unit of Kerinci Regency. Researchers collected data through interviews, observation and documentation involving subjects consisting of members of the Civil Service Police Unit and the community in the Kerinci area. The research results show that the communication strategies for Civil Service Police Unit members include: preparing communicative and supportive members as communicators, conducting briefings, carrying out repressive socialization twice, taking action against people who still violate, providing guidance, and handing over criminal acts to the police. The obstacles faced are unprofessional human resources, indicated by: inappropriate educational background, not having experience in the Civil Service sector, and a lack of training so that they do not control the scope for Civil Service Police Unit and find it difficult to advance. Recommendations to the Regent of Kerinci Regency and Heads of Units to formulate policies to improve Human Resources management starting from recruitment, providing education and training, and improving member welfare.